Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.2340/00015555-2803
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Therapist-guided Internet-based Cognitive-behavioural Treatment for Psoriasis and Rheumatoid Arthritis: Two Case Reports

Abstract: Chronic somatic conditions, such as psoriasis, arthritis psoriatica and rheumatoid arthritis, have a large impact on patients' lives. Tailored therapist-guided internet-based cognitive-behavioural therapy (ICBT) has been shown to be effective in improving physical and psychological well-being in these patients. Two cases are presented here, in order to provide an in-depth illustration of the course and content of this novel treatment and to investigate the therapeutic alliance in an online treatment. After fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(42 citation statements)
references
References 42 publications
(53 reference statements)
1
40
0
1
Order By: Relevance
“…In addition, our findings revealed that it is important to have a clear-cut plan B if the technology or internet connection fails, as it could leave the patient vulnerable. In line with findings from studies on telemental health [ 11 ] and internet-based cognitive behavioral therapy [ 48 ], this study found that videoconferencing facilitated the therapeutic alliance as well as same-room counselling.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, our findings revealed that it is important to have a clear-cut plan B if the technology or internet connection fails, as it could leave the patient vulnerable. In line with findings from studies on telemental health [ 11 ] and internet-based cognitive behavioral therapy [ 48 ], this study found that videoconferencing facilitated the therapeutic alliance as well as same-room counselling.…”
Section: Discussionsupporting
confidence: 86%
“… van Beugen et al, 2016 [ 63 ] ICBT and standard care Prospective RCT 6 mo 131: 65 Therapy 66 Control 67M/64F 52.69 // 53.45 18.03 y // 15.16 y Standard care PASI, SAPASI, ISDL, RAND-36 Larger improvements in ICBT compared to CAU regarding physical functioning and impact on daily activities, though not in psychological functioning, at 6-mo follow-up. Spillekom-Van Koulil, 2018 [ 64 ] ICBT Case report 5 mo/6 mo 2 1M/1F 64/26 28 y/1 y N/A NS Improved physical and psychological wellbeing, sustained at 6-mo follow-up. Bundy et al, 2013 [ 65 ] eTIPs—CBT Prospective RCT 6 w 126: 61 Therapy 65 Control 59M/67F 45 >16 y usual care PASI, HADS, DLQI No significant difference in PASI scores after intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Mindfulness-based cognitive therapy MBCT and its variants, mindfulness-based self-compassion therapy (MBSCT), and self-help MBSCT (MBSCT-SH), have yielded positive results, though mixed in comparison with treatment as usual [ 61 , 62 ]. Similarly, internet-based cognitive behavioral therapy (ICBT) managed to improve physical functioning and diminish the impact of psoriasis on everyday activities in patients presenting a psychological risk profile, and also enhanced and maintained psychological wellbeing [ 63 , 64 ]. Based on the RCT by Bundy et al, a web-based online electronic Targeted Intervention for Psoriasis (eTIPs), also a form of cognitive-behavioral therapy, did not achieve a significantly different result when compared to standard care, yet, as the authors mentioned, the results were constrained by a large quantum of missing data [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…All three studies (47,51,58) measuring affect detected positive results. One study (47) observed significant improvements in mean scores on the emotion subscale of ItchyQoL in people with atopic dermatitis, psoriasis and chronic itch through an educational website called Interactive Toolbox of Comprehensive Health Resources to Enhance Living with Itch (ITCH RELIEF) from baseline to 1 month (33.4 vs. 31.5, p < 0.01).…”
Section: Moodmentioning
confidence: 90%